Calcium stearate: A green corrosion inhibitor for steel in concrete environment - Quraishi M.A.; Kumar V.; Abhilash P.P.; Singh B.N. (My University, 2025)
In the present investigation the effect of calcium stearate on corrosion of steel was investigated. The effect of inhibitor on consistency, soundness, setting times of cement, compressive strength cement and concrete was also studied.The results of the investigation demonstrated that calcium Stearate is an effective inhibitor.It showed 90 %and 93%IE at the concentration of 3 and 5% respectively. The addition of Inhibitor acts as accelerator for setting time and slow down compressive strength at early stage. After 60 days strength is improve significantly. Petrographic examination reveals that calcium Stearate blocks the pores and thereby reduces the corrosion rate of steel. In photographic examination inhibited steel is found to be more smooth as compared to blank.